Reduction of 75% in the Psoriasis Area and Severity Index (PASI) for Moderate-to-Severe Psoriasis Vulgaris - Nahrisyah, Nahrisyah; Nababan, Kristo A. (CoinReads Media Prima, 2025)
Introduction: Psoriasis vulgaris is a chronic inflammatory skin disorder characterized by the presence of scaly, red plaques. The severity of the condition is often evaluated using the Psoriasis Area and Severity Index (PASI), which quantifies the extent and severity of skin lesions. A treatment is considered successful when a PASI 75 is achieved, indicating a 75% reduction in the PASI score. Case: A 26-year-old female presented with itchy and scaly red plaques covering nearly her entire body for the past month. Upon examination, her initial PASI score was 21.8. The patient was treated with a combination of systemic and topical therapies, resulting in a significant clinical improvement. Within two months, the patient achieved a PASI 75, demonstrating a 75% reduction in the PASI score. Conclusion: This case underscores the importance of achieving PASI 75 as a critical treatment goal in both clinical practice and research. It highlights the potential of effective therapy in managing psoriasis vulgaris and serves as a guide for dermatologists in optimizing treatment strategies for psoriasis patient.